A pathological case caused by Philometra madai Quiazon, Yoshinaga & Ogawa, 2008 (Nematoda: Philometridae) in the ovary of the onespot snapper fish Lutjanus monostigma (Teleostei, Lutjanidae) from the Red Sea - Al-Jahdali, Mohammed O. (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
Lutjanus spp. (Teleostei, Lutjanidae) rarely recorded as hosts of gonad-infecting species of Philometra Costa, 1845 (Nematoda: Philometridae). Here, gravid females of Philometra madai Quiazon, Yoshinaga & Ogawa, 2008 which parasitizes the ovary of the bream Pagrus major (Teleostei, Sparidae) and the only species of the genus described from the Red Sea fishes, is recorded for the first time from the ovary of the onespot snapper fish Lutjanus monostigma (Cuvier, 1828) (Teleostei, Lutjanidae). Histopathological changes in the ovary of this fish associated with this infection were significant, and may thus affect the reproductive potential and success of the fish.